Suitability and uptake of vaccines in the last 4 weeks among child participants of a health screening campaign - Devaraj, Navin Kumar (University of Malta, Medical School, 2023)
INTRODUCTION: Vaccine can be described as a tool available to parents to protect their infants and children from potentially deadly diseases. It can prevent deaths and save lives at the same time. This study was aimed at the suitability and uptake of vaccines in the last 4 weeks among child participants of a health screening campaign. METHODS: A cross-sectional, prospective observational study was conducted at two communities through health campaign. A validated and self-administered questionnaire that includes two sections on socio-demographic details and a section on child vaccination practices was used. Statistical Package for Social Sciences v26.0 was used for data analysis. RESULTS: The mean age is 50.1±22.7 years. Majority were females (68.3), of Chinese ethnicity (21.7), married (73.3) and not employed (75.0). Majority had none or primary level of education only (60.0). Majority of the children were suitable to receive vaccine i.e. 58/60 or 96.7. CONCLUSION: The uptake of children in receiving vaccine is high. This augurs well for a nation keen to have healthy citizens that can spur the economy.